ANALISIS FAKTOR-FAKTOR PENYEBAB ANAK TIDAK MELANJUTKAN PENDIDIKAN MENENGAH DI DESA BAGAN BHAKTI KECAMATAN BALAI JAYA KABUPATEN ROKAN HILIR - Julyanti, Ningrum; ', Hambali; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted in the village of Bagan Bhakti Jaya subdistrict Hall Rokan Hilir. The background of this study is still the presence of children who are not melajutkan secondary education. This can be seen in data from the Village office Bagan Bhakti children who do not continue secondary education numbered 21 people at age 11-15 years. The problem of this research is what are the factors that cause children do not continue secondary education (middle and high school) in the village of Bagan Bhakti districts Balai Jaya subdistrict Hall Rokan Hilir. This study aims to determine the factors that cause children do not continue secondary education (middle and high school) in the village of Bagan Bhakti districts Balai Jaya subdistrict Hall Rokan Hilir. As for the population in this study were all children who do not continue secondary education at the age of 11-15 years in the village of Bagan Bhakti Central District of Rokan Hilir districts Balai Jaya totaling 21 people, while the sample in this research is the students complete primary school by 9 people, and as many as 12 students graduated from the junior high school. A sampling technique that uses total sampling technique. The technique of collecting data were collected through observation, questionnaires, interviews, literature, and documentation. Results of research on Analysis of Causes Children No Continuing Secondary Education In the village of Bagan Bhakti Jaya subdistrict Hall Rokan Hilir in the can that be a contributing factor is boredom with the percentage of 71.43% and the economic situation of families with the percentage of 80.95%.Keywords: Factors contributing, children don’t go on secondary education